Kajian karakteristik aerodinamis turbin hidrokinetik Savonius dengan 2 semicircular blade-rounded leading edge - Rozi, K.; Fajar, T.K.B.; Farras, A.Z. (Universitas Mataram, 2022)
This numerical work was carried out to investigate the flow field characteristics through Savonius hydeokinetic turbine with 2 smicircular blade-rounded leading edge. The effects of blade thickness, and freestream velocity were simulated using ANSYS FLUENT with k-w SST model. The results show that the structure of the flow changes with increasing turbine rotation. The coefficient of torque and power for thin blades is higher than for thicker turbine blades and its values increase with the increase in the freestream velocity. The turbin wirh thin blade thickness better than with thick blade thickness